Porous ferroferric oxide symmetric capacitor and preparation method and application thereof

By using porous iron tetraoxide material as electrode material and combining with the preparation method of carbon material substrate, the problem of low energy density of existing supercapacitors is solved, and a supercapacitor with high specific capacitance and high energy density is achieved, with good cycle stability and service life.

CN119650311AActive Publication Date: 2025-03-18JILIN UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411774833.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-18
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

The low energy density of existing supercapacitors limits their commercial application and development, especially the low specific capacity contribution of carbon material negative electrodes and the limitation of hydrogen evolution and oxygen evolution potential.

Method used

Porous iron tetraoxide material is used as electrode material, and prepared by hydrothermal pore formation method and electrochemical conversion method. Combined with a carbon material substrate, a porous iron tetraoxide material loaded on the carbon substrate is formed, and assembled as a positive and negative electrode material.

Benefits of technology

High specific capacitance and high energy density are achieved. The specific capacity of the supercapacitor can reach 200-300F/g, the energy density can reach 110-160Wh/kg, and it has good cycle stability and service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650311A_ABST
    Figure CN119650311A_ABST
Patent Text Reader

Abstract

The invention is suitable for the technical field of chemical power sources, and provides a preparation method of a porous ferroferric oxide symmetric capacitor, which comprises the following steps: putting an iron source salt solution, a pore-forming additive and a carbon material substrate subjected to surface treatment into a reaction kettle, putting the reaction kettle into a drying oven, carrying out hydrothermal reaction, and after the hydrothermal reaction is finished, obtaining a porous ferroferric oxide symmetric capacitor; the porous iron trioxide carbon material is obtained; performing electrochemical conversion on the porous ferric oxide-carbon material by adopting a cyclic voltammetry method to obtain a flexible porous ferroferric oxide-carbon material; and taking the porous ferroferric oxide and carbon material as a positive electrode material and a negative electrode material respectively, taking two electrode clamps to clamp the positive electrode material and the negative electrode material respectively, placing the positive electrode material and the negative electrode material in an electrolytic tank containing a neutral salt solution, and assembling to obtain a supercapacitor monomer. The invention also provides a symmetric capacitor of porous ferroferric oxide and an application thereof. The capacitor has the advantages of high specific capacitance, high energy density, good cycling stability, long service life and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical power sources, and in particular relates to a porous ferroferric oxide symmetrical capacitor and a preparation method and application thereof. Background Art

[0002] Compared with batteries, supercapacitors have the advantages of higher charge and discharge current density, higher power density, higher cycle stability and environmental friendliness. They are efficient energy storage devices with broad application prospects. Among them, aqueous symmetrical supercapacitors have the advantages of low cost, easy assembly and operation, and have received widespread attention. However, compared with secondary batteries, supercapacitors have lower energy density, which limits their commercial application and development. Therefore, the key research on supercapacitors is mainly to improve their energy density, such as using metal oxides (hydroxides) with high specific capacitance with pseudocapacitive properties as electrode materials, and matching them with carbon materials with double electrical layer properties to form supercapacitors. Although its energy density has been improved to a certain extent, it is still far lower than that of batteries. On the one hand, it is attributed to the limitation of hydrogen and oxygen evolution potential, and on the other hand, it is attributed to the lower specific capacity contribution of carbon material negative electrode.

[0003] The voltage range of existing supercapacitors in aqueous alkaline or acidic electrolytes is around 1.5V, while that in neutral electrolytes can be extended to 2.0V. Using high-specific-capacity metal oxides instead of carbon materials as negative electrodes can increase the energy density from 30-50Wh / kg to over 80Wh / kg, but the desired specific capacitance and energy density have not yet been achieved. Summary of the invention

[0004] The purpose of the embodiments of the present invention is to provide a method for preparing a porous ferroferric oxide symmetrical capacitor, aiming to solve the problems raised in the above background technology.

[0005] The embodiment of the present invention is implemented as follows: a method for preparing a porous ferroferric oxide symmetrical capacitor comprises the following steps:

[0006] (1) placing an iron source salt solution, a pore-forming additive and a surface-treated carbon material substrate into a reactor and placing the reactor in an oven for hydrothermal reaction, and after the hydrothermal reaction is completed, a porous iron oxide@carbon material is obtained;

[0007] (2) Electrochemically converting the porous Fe2O3@carbon material using cyclic voltammetry to obtain a flexible porous Fe3O4@carbon material;

[0008] (3) The porous ferroferric oxide@carbon material is used as the positive electrode material and the negative electrode material respectively, and the positive and negative electrode materials are clamped by two electrode clips respectively, and placed in an electrolytic cell filled with a neutral salt solution to assemble a supercapacitor monomer;

[0009] (4) The supercapacitor monomers can be connected in series or in parallel as required.

[0010] Preferably, in step (1), the carbon material substrate is one of carbon fiber cloth, carbon fiber felt, and graphite;

[0011] The surface treatment is specifically as follows: ultrasonically cleaning the carbon material substrate in acetone, ethanol and deionized water in sequence for 1 to 2 hours, and then drying the cleaned carbon material substrate.

[0012] Preferably, in step (1), the iron source salt solution is a ferric nitrate solution, and the concentration of the ferric nitrate solution is 50-75 mmol / L;

[0013] The pore-forming additive is one of oxalic acid, sodium oxalate and potassium oxalate.

[0014] Preferably, in step (1), the temperature of the hydrothermal reaction is 180-200° C. and the time is 23-25 ​​h.

[0015] Preferably, in step (2), the electrochemical conversion is specifically as follows: the porous ferric oxide @ carbon material is cut and fixed with an electrode clamp, a platinum sheet is used as a counter electrode, a calomel electrode is used as a reference electrode, and a 2M potassium hydroxide solution is used as an electrolyte. The scan rate is set to 2 mV / s, the number of turns is 20, and the potential window is -1.2-0 V. The porous ferric oxide @ carbon material is completely electrochemically converted. After completion, it is taken out, cleaned with deionized water, and then dried.

[0016] Preferably, in step (3), the neutral salt solution is one or more of potassium chloride, potassium sulfate, and potassium nitrate, and the concentration of the neutral salt solution is 1-6 mol / L.

[0017] Another object of an embodiment of the present invention is to provide a symmetrical capacitor of porous ferroferric oxide, which is prepared by the above-mentioned preparation method.

[0018] Another object of an embodiment of the present invention is to provide an application of a porous ferrosoferric oxide symmetrical capacitor in the preparation of wearable electronic devices.

[0019] The present invention provides a method for preparing a porous symmetrical ferroferric oxide capacitor, wherein a porous ferroferric oxide material supported on a carbon substrate is prepared by a hydrothermal pore-forming method and an electrochemical conversion method, without the additional addition of a binder and a conductive agent, and the film thickness and pore size distribution are uniform. The carbon substrate material has good bonding and compatibility with the hydrothermally grown iron oxide. The ferroferric oxide electrode after electrochemical conversion has good electrochemical stability, high electrochemical activity, rich specific surface area, good electrical conductivity, and high specific capacitance, providing a key element for a high-energy supercapacitor. Specifically, the specific capacitance can reach 1500-2000F / g, so that the assembled symmetrical supercapacitor has a higher specific capacity, which can reach 200-300F / g, and also has an ultra-high energy density, which can reach 110-160Wh / kg.

[0020] The positive potential range of the pure porous ferroferric oxide electrode is 0-1.0V, and the negative potential range is -1.2V-0V. The prepared symmetrical supercapacitor widens the working potential range to 0-2.0V, has a higher energy density, and its cycle stability is also high. At a current density of 10A / g, after 3000 cycles, the supercapacitor still has a large energy density, which is 85.1% of the initial energy density.

[0021] The materials used are common, the preparation process is easy to implement, and it is environmentally friendly. The hydrothermal pore-forming process can batch-prepare ferroferric oxide materials with different loading amounts, and only a small mass and volume can be used to achieve high energy and high power requirements.

[0022] The positive and negative electrodes of the embodiments of the present invention use the same electrolyte, and multiple supercapacitor cells can share the same electrolyte, saving the amount of electrolyte. The flexibility of the carbon substrate also allows the supercapacitor device to be bent without affecting its performance, greatly improving the service life of the device and showing great potential for powering wearable electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The electrode area provided in Example 1 of the present invention is 1 cm 2 Cyclic voltammetry curve of porous ferroferric oxide electrode at a scan rate of 10 mV / s (negative potential range);

[0024] Figure 2 The electrode area provided in Example 1 of the present invention is 1 cm 2 The constant current charge-discharge curve of the porous ferroferric oxide electrode at 2A / g (negative potential range);

[0025] Figure 3 The electrode area provided in Example 1 of the present invention is 1 cm 2Cyclic voltammetry curve of porous ferroferric oxide electrode at a scan rate of 10 mV / s (positive potential range);

[0026] Figure 4 The electrode area provided in Example 1 of the present invention is 1 cm 2 Constant current charge-discharge curve of the porous ferroferric oxide electrode at 2A / g (positive potential range);

[0027] Figure 5 The cyclic voltammetry curve of the symmetrical supercapacitor provided in Example 1 of the present invention at a scan rate of 10 mV / s;

[0028] Figure 6 The charge and discharge curve of the symmetrical supercapacitor provided in Example 1 of the present invention at a current density of 2A / g;

[0029] Figure 7 The variation curve of power density and energy density of the symmetrical supercapacitor provided in Example 1 of the present invention;

[0030] Figure 8 The charge and discharge curves of the symmetrical supercapacitor provided in Example 1 of the present invention at different current densities;

[0031] Fig. 9 The cycle stability results of the symmetrical supercapacitor provided in Example 1 of the present invention at 5000 charge and discharge cycles;

[0032] Fig.10 The AC impedance spectrum of the symmetrical supercapacitor provided in Example 1 of the present invention;

[0033] Fig.11 XRD patterns of the porous iron oxide @ carbon cloth sample and the porous ferroferric oxide @ carbon cloth sample provided in Example 1 of the present invention;

[0034] Fig.12 Transmission electron microscope morphology images of the porous iron oxide @ carbon cloth sample (left) and the porous ferroferric oxide @ carbon cloth sample (right) provided in Example 1 of the present invention;

[0035] Fig.13 The charge and discharge curves of the synthetic porous ferroferric oxide sample and the non-porous ferroferric oxide sample provided in Example 1 of the present invention at a current density of 4 A / g. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0037] A symmetrical capacitor of porous ferroferric oxide, the preparation method of which comprises the following steps:

[0038] (1) Select one of carbon fiber cloth, carbon fiber felt, and graphite to perform surface treatment on the carbon material substrate, specifically: ultrasonically clean in acetone, ethanol, and deionized water for 1-2 hours in turn to remove organic or inorganic impurities on the surface of the carbon material, then place the cleaned carbon material substrate in a constant temperature drying oven at 60°C for 6 hours, put an iron source salt solution (2mmol of ferric nitrate + 40mL deionized water or 3mmol of ferric nitrate + 40mL deionized water), a pore-forming additive (3mmol of oxalic acid, 4mmol of sodium oxalate, 4mmol of potassium oxalate) and the treated carbon material substrate into a reactor and place it in an oven for hydrothermal reaction (190°C, 24 hours), and after the hydrothermal reaction is completed, a porous iron oxide@carbon material is obtained;

[0039] (2) The porous ferric oxide @ carbon material was electrochemically converted by cyclic voltammetry, specifically: the porous ferric oxide @ carbon material was cut into 1 cm * 1.5 cm size and fixed with an electrode clamp, a platinum sheet was used as a counter electrode, a calomel electrode was used as a reference electrode, and a 2M potassium hydroxide solution was used as an electrolyte. The scan rate was set to 2 mV / s, the number of cycles was 20, and the potential window was -1.2-0 V. The ferric oxide @ carbon material was completely electrochemically converted. After the conversion, the electrode sheet was taken out, cleaned with deionized water, and then placed in a constant temperature drying oven at 60 ° C for more than 6 hours to completely convert the ferric oxide into ferric oxide and retain the porous particle morphology to obtain a porous ferric oxide @ carbon material, which was used as a flexible positive electrode and a flexible negative electrode of a capacitor;

[0040] (3) Take two electrode clips to clamp the positive and negative electrodes respectively, fix them to the appropriate position of the electrolytic cell cover through a rubber ring, and then place them in an electrolytic cell containing a neutral salt solution (one or more of potassium chloride, potassium sulfate, and potassium nitrate, with a concentration of 1-6 mol / L) to assemble a supercapacitor monomer, in which the positive and negative electrodes are placed in parallel at the same height in the electrolytic cell. The volume of the electrolyte changes according to the volume of the electrolytic cell, the size and number of the electrodes, and the area of ​​the monomer electrode can be 1-20 cm 2 , the electrolyte volume of a single supercapacitor is 5-200mL;

[0041] (4) Supercapacitor monomers are connected in series or in parallel to form a supercapacitor combination circuit as needed to achieve the required operating current and voltage.

[0042] During the charge and discharge process, porous ferroferric oxide provides pseudocapacitance through Faraday reaction and electrostatic adsorption capacitance through high specific surface area, and has a potential working window as wide as 2.0V, thereby improving the energy density of the supercapacitor. Since the porous ferroferric oxide material undergoes a quasi-reversible redox reaction, the prepared symmetrical supercapacitor has good cycle stability and service life. Flexible carbon material is used as the substrate to ensure that the active substance fully participates in the reaction, thereby improving the mass energy density of the overall supercapacitor device and having good toughness and bending resistance.

[0043] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.

[0044] Embodiment 1: A symmetrical capacitor of porous ferroferric oxide, the preparation method of which comprises the following steps:

[0045] (1) A carbon fiber cloth with an area of ​​2 cm*3 cm was used as a substrate, and was soaked in acetone for 30 minutes, ethanol for 30 minutes, and deionized water for 30 minutes. The treated carbon cloth was placed in a constant temperature drying oven and dried at 60°C for 6 hours. A porous iron oxide precursor sample was synthesized by hydrothermal reaction. The hydrothermal solution was configured as 3 mmol iron nitrate + 40 mL deionized water. The hydrothermal temperature was 190°C, the hydrothermal time was 24 hours, and the pore-forming additive was 3 mmol oxalic acid. The porous iron oxide @ carbon cloth sample was obtained by hydrothermal synthesis. After cleaning, it was placed in a constant temperature drying oven and dried at 60°C for 6 hours. The iron oxide loading was about 1.0 mg / cm 2 ;

[0046] (2) The porous iron oxide @ carbon cloth sample was in situ electrochemically activated by electrochemical oxidation. An electrochemical three-electrode system was assembled with a porous iron oxide @ carbon cloth with an area of ​​1 cm*1.5 cm as the working electrode, a platinum sheet as the counter electrode, and a calomel electrode as the reference electrode. Cyclic voltammetry was used as the activation method with a scan rate of 2 mV / s, 20 cycles, and a potential window of -1.2-0 V to completely convert it into a porous ferroferric oxide @ carbon cloth sample. After cleaning, it was placed in a constant temperature drying oven at 60°C for 6 hours. As a flexible electrode, the ferroferric oxide loading was about 1.0 mg / cm 2 ;

[0047] (3) Prepare 50 mL of 2 mol / L KCl as the electrolyte and use an electrochemical cell to assemble an electrode with an area of ​​1 cm 2 Symmetric supercapacitor.

[0048] Comparative Example 1: A nonporous ferroferric oxide@carbon cloth electrode material, the preparation method of which comprises the following steps:

[0049] (1) A carbon cloth with an area of ​​2 cm*3 cm was used as a substrate, and the carbon cloth was soaked in acetone for 30 minutes, in ethanol for 30 minutes, and in deionized water for 30 minutes. The treated carbon cloth was placed in a constant temperature drying oven and dried at 60°C for 6 hours. The iron oxide precursor sample was synthesized by hydrothermal reaction. The hydrothermal solution was configured as 3 mmol iron nitrate + 40 mL deionized water. The hydrothermal temperature was 190°C and the hydrothermal time was 24 hours. The hydrothermal synthesis obtained a non-porous iron oxide @ carbon cloth sample. After cleaning, the carbon cloth was placed in a constant temperature drying oven and dried at 60°C for 6 hours. The iron oxide loading was about 1.0 mg / cm 2 ;

[0050] (2) The iron oxide @ carbon cloth sample was in situ electrochemically activated by electrochemical oxidation method. An electrochemical three-electrode system was assembled with a non-porous iron oxide @ carbon cloth with an area of ​​1 cm*1.5 cm as the working electrode, a platinum sheet as the counter electrode, and a calomel electrode as the reference electrode. Cyclic voltammetry was used as the activation method with a scan rate of 2 mV / s, 20 cycles, and a potential window of -1.2-0 V to completely convert it into a non-porous iron oxide @ carbon cloth sample. After cleaning, it was placed in a constant temperature drying oven at 60°C for 6 hours to obtain a flexible non-porous iron oxide @ carbon cloth electrode material.

[0051] Performance Test:

[0052] The porous iron oxide @ carbon cloth sample and the porous ferroferric oxide @ carbon cloth sample synthesized in Example 1 were analyzed by XRD diffractometer, and the XRD patterns were as follows: Fig.11 As shown; the morphology is obtained by transmission electron microscopy analysis. Fig.12 As shown in the figure, it can be seen that the particle size of the porous iron oxide @ carbon cloth sample is about 40nm, and the porous ferroferric oxide @ carbon cloth sample maintains the original particle morphology and particle size.

[0053] The flexible electrode prepared in Example 1 was subjected to a cyclic voltammetry test at a scanning rate of 10 mV / s, and a cyclic voltammetry curve in the negative potential range was obtained as shown in FIG. Figure 1 As shown, the cyclic voltammetry curve in the positive potential interval is as follows Figure 3 As shown; the flexible electrode was charged and discharged with a current density of 2A / g, and the constant current charge and discharge curve in the negative potential range was obtained as shown Figure 2 As shown, the constant current charge and discharge curve in the positive potential interval is as follows Figure 4 As shown;

[0054] The symmetrical supercapacitor prepared in Example 1 was subjected to a cyclic voltammetry test at a scan rate of 10 mV / s, and the cyclic voltammetry curve was as follows: Figure 5 As shown;

[0055] The symmetrical supercapacitor prepared in Example 1 was subjected to constant current charge and discharge test, and the charge and discharge curves were as follows: Figure 6 As shown, the maximum potential window is 2.0V. When the current density is 2A / g, the specific capacitance, energy density and power density of the supercapacitor are 284.4F / g, 158.0Wh / kg and 2.0kW / kg respectively.

[0056] The symmetrical supercapacitor prepared in Example 1 was subjected to charge and discharge tests at different current densities to obtain a relationship curve between energy density and power density as shown in the figure: Figure 7 As shown, the charge and discharge curves under different current densities are Figure 8 As shown, the maximum potential window is 2.0V. When the current density is 2A / g, the energy density and power density of the supercapacitor are 158.0Wh / kg and 2.0kW / kg respectively; when the current density is 4A / g, the energy density and power density of the supercapacitor are 145.1Wh / kg and 4.0kW / kg respectively; when the current density is 6A / g, the energy density and power density of the supercapacitor are 133.6Wh / kg and 6.0kW / kg respectively; when the current density is 10A / g, the energy density and power density of the supercapacitor are 113.3Wh / kg and 10kW / kg respectively; when the current density is 15A / g, the energy density and power density of the supercapacitor are 90.0Wh / kg and 15kW / kg respectively. It can be seen from the relationship between power density and energy density that energy density is inversely proportional to power density.

[0057] The symmetrical supercapacitor prepared in Example 1 was tested for cycle stability, and the results were as follows: Fig. 9 As shown, the maximum potential window is 2.0V. When the current density is 10A / g, the initial specific capacity is 117.3mAh / g. After 5000 cycles of charge and discharge, the energy density of the supercapacitor is 78.6% of the initial energy density. Specifically, after 1000 cycles of charge and discharge, the energy density of the supercapacitor is 93.1% of the initial energy density; after 3000 cycles of charge and discharge, the energy density of the supercapacitor is 85.1% of the initial energy density; after 5000 cycles of charge and discharge, the energy density of the supercapacitor is 78.6% of the initial energy density, indicating that the supercapacitor has good cycle stability.

[0058] The symmetrical supercapacitor prepared in Example 1 was subjected to EIS test, and the AC impedance spectrum was obtained as shown in Fig.10 As shown, it can be seen that the porous ferroferric oxide electrode material has a lower charge transfer resistance and presents a more efficient charge storage capacity;

[0059] The porous ferroferric oxide @ carbon cloth sample prepared in Example 1 and the non-porous ferroferric oxide @ carbon cloth sample prepared in Comparative Example 1 were subjected to a constant current charge-discharge test at a current density of 4 A / g, and the charge-discharge curves were obtained as shown in FIG. Fig.13 As shown, it can be seen that the porous ferroferric oxide@carbon cloth sample prepared in the embodiment of the present invention has a stronger energy storage capacity and can store more electricity under the same conditions.

[0060] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a porous ferroferric oxide symmetrical capacitor, characterized in that: The following steps are involved: (1) placing an iron source salt solution, a pore-forming additive and a surface-treated carbon material substrate into a reactor and placing the reactor in an oven for hydrothermal reaction, and after the hydrothermal reaction is completed, a porous iron oxide@carbon material is obtained; (2) Electrochemically converting the porous Fe2O3@carbon material using cyclic voltammetry to obtain a flexible porous Fe3O4@carbon material; (3) The porous ferroferric oxide@carbon material is used as the positive electrode material and the negative electrode material respectively, and the positive and negative electrode materials are clamped by two electrode clips respectively, and placed in an electrolytic cell filled with a neutral salt solution to assemble a supercapacitor monomer; (4) The supercapacitor monomers can be connected in series or in parallel as required.

2. The method for preparing a symmetrical capacitor of porous ferroferric oxide according to claim 1, characterized in that: In step (1), the carbon material substrate is one of carbon fiber cloth, carbon fiber felt, and graphite; The surface treatment specifically includes: ultrasonically cleaning the carbon material substrate in acetone, ethanol and deionized water in sequence for 1-2 hours, and then drying the cleaned carbon material substrate.

3. The method for preparing a symmetrical capacitor of porous ferroferric oxide according to claim 1, characterized in that: In step (1), the iron source salt solution is a ferric nitrate solution, and the concentration of the ferric nitrate solution is 50-75 mmol / L; The pore-forming additive is one of oxalic acid, sodium oxalate and potassium oxalate.

4. The method for preparing a symmetrical capacitor of porous ferroferric oxide according to claim 1, characterized in that: In step (1), the temperature of the hydrothermal reaction is 180-200° C. and the time is 23-25 ​​hours.

5. The method for preparing a symmetrical capacitor of porous ferroferric oxide according to claim 1, characterized in that: In step (2), the electrochemical conversion is specifically as follows: the porous ferric oxide @ carbon material is cut and fixed with an electrode clamp, a platinum sheet is used as a counter electrode, a calomel electrode is used as a reference electrode, and a 2M potassium hydroxide solution is used as an electrolyte. The scan rate is set to 2mV / s, the number of turns is 20, and the potential window is -1.2-0V. The porous ferric oxide @ carbon material is completely electrochemically converted. After completion, it is taken out, cleaned with deionized water, and then dried.

6. The method for preparing a symmetrical capacitor of porous ferroferric oxide according to claim 1, characterized in that: In step (3), the neutral salt solution is one or more of potassium chloride, potassium sulfate, and potassium nitrate, and the concentration of the neutral salt solution is 1-6 mol / L.

7. A symmetrical capacitor of porous ferroferric oxide, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 6.

8. Use of the porous ferroferric oxide symmetrical capacitor according to claim 7 in the preparation of wearable electronic devices.

Citation Information

Patent Citations

  • A flexible electrode, a preparation method and an application thereof

    CN109065371A

  • Self-support porous Fe2O3 nanorod array electrocatalyst and preparation method thereof

    CN110721687A